Pengaruh Pengalaman Usaha dan Strategi Promosi Viral terhadap Peningkatan Penjualan Produk Usaha Mikro Kecil Ditinjau dari Perspektif Bisnis Islam : (Studi Pada Usaha Mikro Kecil Kuliner di Kota Bandar Lampung) - Ari Muhamad Rijki; Weny Rosilawati; Supaijo Supaijo (Universitas 45 Surabaya, 2024)
This research aims to determine the influence of business experience and viral promotion strategies on increasing sales of micro and small culinary business products in Bandar Lampung City. This type of research is descriptive research. Descriptive research is research that is directed at providing symptoms, facts or events systematically and accurately, regarding the characteristics of a particular population or area. The sampling technique in this research uses data collection techniques: Library Research and Questionnaires. The research results used partial hypothesis testing (t test) which showed that business experience had a significant negative effect on increasing sales. Viral promotion strategies have a positive and significant effect on increasing sales. Simultaneous hypothesis testing (f test) shows